Paleopedology of ferricrete horizons around Chennai, Tamil Nadu, India - Hema Achyuthan (Revista Mexicana de Ciencias Geológicas)
Some soils around Chennai, Tamil Nadu, are represented by ferricrete horizons, and these can be related to the underlying bedrock. In the present study, Red Soils and ferricretes have been studied from four different sites: Red Hills, Vaiyapur, Uttukkadu, and Pallavaram, which were formed from different parent rocks. Red Soils and ferricretes around Vaiyapur and Red Hills are formed from the Upper Gondwana sandstone and shale, while around Pallavaram they are formed from Precambrian charnockites. In this paper, morphology, micromorphology, and geochemistry of ferricretes and Red Soils are presented.